Durability of seawater sea sand concrete beams reinforced with carbon nanotube-modified BFRP bars in a marine environment. (15th July 2022) - Su, Chang; Wang, Xin; Ding, Lining; Wu, Zhishen; Ma, Xiaoguang
Abstract: In this study, the durability of seawater sea sand concrete (SWSSC) beams reinforced with basalt fiber-reinforced polymer (BFRP) bars in a marine environment was investigated. To improve the durability of the SWSSC beams, different types of reinforcements, namely, carbon nanotube (CNT)-modified BFRP longitudinal bars, CNT-modified BFRP stirrups, and sand-coated BFRP stirrups, were introduced to replace steel bars and ordinary BFRP bars. Moreover, the durability of the CNT-modified BFRP bars under an SWSSC environment and the durability of the bond strength between the CNT-modified BFRP bars/sand-coated BFRP bars and SWSSC under the marine environment were assessed. The results showed that the modification using CNTs effectively slowed down the degradation rate of the tensile strength of the BFRP bar and the bond strength between the BFRP bar and SWSSC concrete in the marine environment. Additionally, the load-carrying capacity of the SWSSC beams reinforced with BFRP bars exhibited obvious degradation after exposure to the seawater environment. With the increase in corrosion age, the SWSSC beams suffered from shear-compression failure owing to the decrease in the bond strength between the BFRP stirrups and the surrounding concrete. Replacing ordinary BFRP stirrups with CNT-modified BFRP stirrups prevented the occurrence of shear-compression failure in the early stage of corrosion, but the effect disappeared after 9 months. A similar improvement in the shear durability of SWSSC beams by using sand-coated BFRP stirrups was also observed.